Structural identification of the operator visual channel - Петрова, Ю.В. (Proceedings of National Aviation University, 2004)
Hire is presented to consider a method of the visual channel structural identification of the operator in the present of the stochastic entrance information, and to estimate some results of structural identification and also estimation criterion of the operator actions efficiency.